If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + x + y = 24 Solving Y + x + y = 24 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-1x' to each side of the equation. Y + x + -1x + y = 24 + -1x Combine like terms: x + -1x = 0 Y + 0 + y = 24 + -1x Y + y = 24 + -1x Add '-1y' to each side of the equation. Y + y + -1y = 24 + -1x + -1y Combine like terms: y + -1y = 0 Y + 0 = 24 + -1x + -1y Y = 24 + -1x + -1y Simplifying Y = 24 + -1x + -1y
| 3-(1/3x^2/3) | | 5n+2(8n-7)= | | 3-((1)/(3x)^2/3) | | 3w+11=-8+51 | | 3-1/3x^2/3 | | -2=-6w+2(w-3) | | 16(2x-7)=4(8x+9) | | 3u+2(u+5)=35 | | 152=-4(7x-3) | | -108=-4(-5b-3) | | xcubo+ycubo=35 | | P^4q^6/p^2q^3 | | 2x^3/2*x^1/7 | | (15a4-9a)/3a | | 4-2x=8+0.5x | | (3+ab)(7-ab)= | | (3+v)(5v-6)=0 | | X+6=6x+31 | | 2+5e=12 | | xcosy=ycosx | | -7=1+n | | y=2/3x-19 | | 10(x-9)-9(5-6x)=2(4x-1)+5(1-2x) | | 4|=/2x-1/=12 | | 16÷8/9 | | (5y+3)(4-y)=0 | | 4c-7=3c-7 | | X+23=5x+31 | | 3+11x=5x+9 | | Ln(14)=ln(x) | | -3x+9=-2(3x+3) | | 18x+33=18x+11 |